The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.bpj.2012.08.021
|View full text |Cite
|
Sign up to set email alerts
|

A Spatial Model for Integrin Clustering as a Result of Feedback between Integrin Activation and Integrin Binding

Abstract: Integrins are transmembrane adhesion receptors that bind extracellular matrix (ECM) proteins and signal bidirectionally to regulate cell adhesion and migration. In many cell types, integrins cluster at cell-ECM contacts to create the foundation for adhesion complexes that transfer force between the cell and the ECM. Even though the temporal and spatial regulation of these integrin clusters is essential for cell migration, how cells regulate their formation is currently unknown. It has been shown that integrin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 65 publications
4
66
0
Order By: Relevance
“…Single-particle tracking studies using the mys b58 (V409D) mutation in S2 cells further support our findings (Mainali and Smith, 2013). In accordance with recent studies on mammalian ILK (Huet-Calderwood et al, 2014;Ye et al, 2013), we cannot exclude the possibility that the reduced integrin immobile fraction at the PM compromises the sustainability of integrin clustering (Welf et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
“…Single-particle tracking studies using the mys b58 (V409D) mutation in S2 cells further support our findings (Mainali and Smith, 2013). In accordance with recent studies on mammalian ILK (Huet-Calderwood et al, 2014;Ye et al, 2013), we cannot exclude the possibility that the reduced integrin immobile fraction at the PM compromises the sustainability of integrin clustering (Welf et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
“…Nestin also regulated the formation of a5b1 clusters, in a FAKrelated fashion, as FAK activity regulated cluster volume in control cells, but had no effect on cluster size or number in nestindownregulated cells. A recent paper describing a spatial model of integrin clustering (Welf et al, 2012) has shown that a small pool of active integrin is required to initiate integrin clustering, which triggers a positive-feedback loop to increase integrin binding and activation. In this context, it is plausible that the increase in integrin activity as a result of nestin downregulation could trigger Quantification of the amount of degraded matrix compared to the area covered by the cells, n53.…”
Section: Discussionmentioning
confidence: 99%
“…Because binding of active (high-affinity state) integrins to the ECM initiates the assembly of adhesions (Hynes, 1992;Welf et al, 2012), Asef2 could affect adhesion turnover by altering the amount of active integrins at the cell membrane. To examine cell surface levels of active b1 integrin, a major integrin that binds to type I collagen, GFP and GFP-Asef2 cells were incubated with HUTS-4 antibody and subjected to flow cytometry.…”
Section: Rac Activity Is Enhanced By Asef2mentioning
confidence: 99%